Analisis Kepatuhan Ibu Dalam Pemberian Imunisasi Polio Pada Anak Di Puskesmas Tanjung Baru Kabupaten. OKU Tahun 2021 - Vima Erwani; Chairil Zaman (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Polio disease is an infectious disease caused by a virus and can be prevented by giving polio immunization to children under five. Around 4% of infants in the world are not fully vaccinated and remain at risk of developing polio. To find out the relationship between maternal compliance in giving polio immunization to children. Cross sectional research design, mothers who have children aged 1 to 5 years who visit the Tanjung Baru Health Center or Pustu or Posyandu in the Tanjung Baru Health Center area, Baturaja Timur District to check the health of their children in 2021. The sampling method is by purposive sampling technique. 100 each respondents. This research was conducted for March 8 – May 3 2021. The data collection used a questionnaire. The results of the statistical analysis of respondents using the Chi-Square test showed that there was a significant relationship (p‹0.05) for the Knowledge and Attitude variables variableFrom this study it was concluded that the Puskesmas should further increase public understanding of polio immunization by providing education in the form of counseling or other information media so that the information can be reached and accepted by the community so that there are no more children under five who are not immunized against polio.